Evidence for a Precursor to Circulating Parathyroid Hormone - Sherwood, Louis M. (1970)
Bovine parathyroid glands incubated in organ culture synthesize and secrete parathyroid hormone in response to physiologic alterations in cation concentration. Hormone synthesized in the glands is immunologically different and higher in molecular weight than that released into the culture medium or circulating in bovine blood, although it is identical to purified hormone extracted from the glands. On the basis of the physiologic responses of tissue and medium hormone to cation, the transfer of radioactive label from one moiety to another, and interconversion of the two forms by a gland homogenate, it is suggested that the parathyroid glands synthesize a precursor hormone (proparathormone) that is modified to the smaller molecule that circulates in blood.